A critical analysis on Malay reserve land in Selangor / Aimi Nadiah Ali … [et al.] - Ali, Aimi Nadiah; Saadudin, Asyraf Wajdi; Abdul Rashid, Izat Nazrin; Mohd Rezuwan, Mohd Amirul (2013)
The thesis is a study on the concept Malay reservation land. This research aims to examine the Malay reservation law in the various states Enactment. The British was the one responsible for introducing the Malay reservation land to protect the Malays. The Malays are bestowed with many privileges. This includes the rights to land ownership. The privileges were given to Malays to safeguard their position as the owners of the land of Malaysia. Critical analysis in the form of literature reviews of the institution of Malay Reserve Enactment and land administrative system of Malaysia is conducted to understand and justified why the institution was introduced. The Malay Reserve Land are facing many inside and outside factors such as the Malays' attitude towards land ownership, past errors from the authorities, and problems related to legal matters. The issues may have been related to the ignorance of rights by the Malays. The information that was gathered through library research was aim to analyze the development of the Malay reservation law in Malaysia. The information was collected to tackle the lack of development of Malay reservation land. The study will also discuss some suggestion to preserve the Malay reservation law.